Hydrogenation catalyst and preparation method and application thereof

By using a support and a hydrogenation catalyst of a long-range ordered Ni-Fe-Cu-M intermetallic compound, the problems of high temperature of alkyne hydrogenation reaction and catalyst deactivation in the prior art are solved, and low temperature efficiency and selectivity are achieved Good hydrogenation reaction significantly improves the stability and performance of the catalyst.

CN119140108APending Publication Date: 2024-12-17EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411164067.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the alkyne hydrogenation reaction, the existing hydrogenation catalysts have problems such as high reaction temperature and easy oligomerization to form ‘green oil’, resulting in catalyst deactivation.

Method used

Using a hydrogenation catalyst including a support and a long-range ordered Ni-Fe-Cu-M intermetallic compound, M is selected from Group VIB, Group IVA or Group VA metal elements by placing the metal element or salt of M with Ni/Fe/ Cu/Mg/Al five-membered layered double hydroxide material is reduced after ion exchange, forming a surfactant site with a unique structure, regulating the spatial structure and electronic structure of the active site, and achieving a low-temperature and efficient hydrogenation reaction.

Benefits of technology

Achieving efficient and selective alkyne hydrogenation under low temperature conditions greatly avoids the formation of 'green oil', improves the activity, selectivity and stability of the catalyst, and solves the limitation of low performance of non-precious metal catalysts sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140108A_ABST
    Figure CN119140108A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a hydrogenation catalyst and a preparation method and application thereof.The hydrogenation catalyst comprises a magnesium-aluminum carrier and a long-range ordered Ni-Fe-Cu-M intermetallic compound, and M is selected from VIB group metal elements, IVA group metal elements or VA group metal elements. In the hydrogenation catalyst disclosed by the invention, four metals, namely Ni, Fe, Cu and M, form a long-range ordered Ni-Fe-Cu-M intermetallic compound and form a Ni-Fe-Cu-M multi-tooth rhombic active site, so that a Ni-Fe-Cu-M quadruple site structure of electron-deficient Ni, electron-deficient Fe and electron-deficient Cu isolated electron-rich M is formed. The hydrogenation catalyst is applied to preparation of olefin through alkyne hydrogenation, high-efficiency and high-selectivity hydrogenation can be achieved under the low-temperature condition, generation of'green oil 'is avoided to a great extent, and the hydrogenation catalyst has the advantages of being high in catalytic activity, good in selectivity and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a hydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] Ethylene and propylene are widely used in the synthesis of a variety of fine chemicals, but the crude ethylene vapor produced by the cracking of petroleum fractions contains 0.5-2.0% volume fraction of acetylene. The trace amount of alkynes present in the process of producing polymerization-grade ethylene is not only a poison to the downstream process catalyst, but also seriously affects the physical properties of the polymer. Therefore, the alkynes at the outlet of the cracking furnace must be removed to reduce the acetylene content to below 5ppm and the propyne content to 5-10ppm. At present, catalytic hydrogenation is the most economical, effective and simple method to remove trace acetylene and propyne from ethylene feed gas. However, the catalytic hydrogenation process has the problem of excessive hydrogenation of alkynes and easy oligomerization to form "green oil", which leads to catalyst deactivation.

[0003] Pd-based traditional bimetallic catalysts have been widely used in catalytic hydrogenation of alkynes. After modification with Au, Cu, Ga, Ag and Zn, the performance of the catalyst can be improved. At present, highly optimized Pd-Ag catalysts are usually used in industry to reduce the activity of deep hydrogenation of acetylene to improve the catalyst selectivity. However, the high cost of Pd-based catalysts has attracted extensive attention in the research of non-precious metal catalysts. Non-metallic Ni can not only be used as an active component for hydrogenation of alkynes in industry, but also has low cost, making it a good choice to replace Pd-based catalysts. However, the ethylene selectivity of Ni-based catalysts is often poor, and other additives need to be introduced to improve the performance of Ni catalysts. For example, the journal J.Am.Chem.Soc.2010,132(12):4321-4327 reported a ternary Cu / Ni / Fe catalyst with high selectivity for olefins. Compared with the commonly used Pd catalyst, the ternary Cu / Ni / Fe catalyst not only greatly improves the olefin selectivity, but also has significant process advantages: high olefin selectivity can be achieved without adding a selectivity enhancer; however, compared with Pd-based catalysts, this catalyst requires a higher reaction temperature, and alkynes are easily oligomerized to form "green oil", resulting in catalyst deactivation. Summary of the invention

[0004] In order to overcome the problems in the prior art of alkyne hydrogenation such as high reaction temperature and easy oligomerization to generate "green oil" which leads to deactivation of the hydrogenation catalyst, a hydrogenation catalyst and a preparation method and application thereof are provided. The hydrogenation catalyst is used for preparing olefins by hydrogenation of alkynes, and can realize efficient alkyne hydrogenation catalytic reaction under low temperature conditions, thus avoiding the generation of "green oil" to a great extent, and has the advantages of high catalytic activity, good selectivity and good stability.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a hydrogenation catalyst, which comprises a carrier and a long-range ordered Ni-Fe-Cu-M intermetallic compound, wherein M is selected from a VIB group metal element, an IVA group metal element or a VA group metal element.

[0006] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst, the method comprising:

[0007] Prepare Ni / Fe / Cu / M / Mg / Al hexalayered double hydroxide material by reacting a metal element of M or a metal salt of M with a Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material, and perform ion exchange on the Ni / Fe / Cu / M / Mg / Al hexalayered double hydroxide material and an alkaline solution before reduction;

[0008] Wherein, M is selected from one of the metal elements of Group VIB, Group IVA or Group VA; and the alkaline solution is selected from a solution containing carbonate ions and / or a solution containing bicarbonate ions.

[0009] The third aspect of the present invention provides a hydrogenation catalyst prepared by the preparation method of the present invention.

[0010] A fourth aspect of the present invention provides a use of the hydrogenation catalyst of the present invention in the hydrogenation of alkynes to produce olefins.

[0011] Through the above technical scheme, in the hydrogenation catalyst of the present invention, the four metals Ni, Fe, Cu and M constitute a long-range ordered Ni-Fe-Cu-M intermetallic compound, constitute a Ni-Fe-Cu-M multi-tooth rhombus active site, and form a Ni-Fe-Cu-M quadruple site structure with electron-deficient Ni, electron-deficient Fe, electron-deficient Cu and isolated electron-rich M.

[0012] In the hydrogenation catalyst of the present invention, the four metals Ni, Fe, Cu and M together constitute a surface active site with a unique structure, and jointly regulate the spatial structure and electronic structure of the active site, thereby forming a Ni-Fe-Cu-M multi-tooth rhombus active site that is beneficial to the adsorption of alkynes (such as acetylene and propyne, etc.), and a Ni active site that is beneficial to the desorption of olefins (such as ethylene and propylene, etc.); wherein the localized electron cloud structure of the active metals Ni, Fe and Cu is regulated by the low electronegativity inert metal M, thereby forming a Ni-Fe-Cu-M quadruple site structure of electron-deficient Ni, electron-deficient Fe and electron-deficient Cu with isolated electron-rich M.

[0013] The hydrogenation catalyst of the present invention is used for hydrogenating alkynes to prepare olefins, and can realize efficient and highly selective hydrogenation under low temperature conditions, thereby avoiding the generation of "green oil" to a great extent, and has the advantages of high catalytic activity, good selectivity and good stability; further, it solves the limitation of low hydrogenation performance of non-precious metal catalysts to a great extent; in particular, it is used for hydrogenating alkynes (acetylene) in olefins (such as ethylene), and can selectively hydrogenate alkynes. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic diagram of the synthesis process of the hydrogenation catalyst of the present invention;

[0015] Figure 2 (a) is the XRD spectrum of Ni3Sn catalyst X1-900 prepared in Example 1, Figure 2 (b) is the XRD spectrum of the Ni-Fe-Cu-Sn catalyst X9-900 prepared in Example 1;

[0016] Figure 3 is a transmission electron microscope (TEM) image of the Ni-Fe-Cu-Sn catalyst X9-900 prepared in Example 1;

[0017] Figure 4 is a transmission electron microscope element analysis photograph of the Ni-Fe-Cu-Sn catalyst X9-900 prepared in Example 1;

[0018] Figure 5 is a high angle annular dark field scanning transmission electron microscope (HAADF-STEM) image of the Ni-Fe-Cu-Sn catalyst X9-900 prepared in Example 1, wherein: Figure 5 (a) is a high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) image. Figure 5 (b) is the line scan elemental analysis diagram of the selected nanoparticles in the corresponding HAADF-STEM image;

[0019] Figure 6 is a spherical aberration electron microscope image of the Ni-Fe-Cu-Sn catalyst X9-900 prepared in Example 1, wherein: Figure 6 (a) Spherical aberration electron microscope image, Figure 6 (b) is the Fourier transform diagram of the catalyst. Figure 6 (c) along Figure 6 (a) The intensity distribution of the atomic image indicated by the arrow, Figure 6 (d) Figure 6 (a) Magnified view of the matrix-marked area and the crystal model corresponding to the

[220] zone axis projection.

[0020] Figure 7It is the GC-MS spectrum of the pyrolysis of green oil on the Ni-Fe-Cu-Sn catalyst X9-900 prepared in Example 1 and the Ni3Sn catalyst X1-900 prepared in Comparative Example 1;

[0021] Figure 8 It is the XRD spectrum of the catalyst prepared in Example 2-5. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] In the context of the present invention and in the embodiments, "green oil" refers to a green transparent liquid formed by the addition of excess hydrogen to alkyne during the hydrogenation process, and is an oligomer of alkyne.

[0024] In the context and embodiments of the present invention, "long-range order" is a professional term to describe the structural characteristics of intermetallic compounds, which are a type of ordered metal materials that are completely different from medium-entropy alloys and high-entropy alloys. The "long-range order" in the present invention refers to a compound composed of metals, which has a long-range ordered crystal structure and basic metal properties different from its constituent elements. The main element atoms of the intermetallic compound are mainly bonded by covalent bonds, and the main element atoms are arranged in a highly ordered manner.

[0025] The first aspect of the present invention provides a hydrogenation catalyst, which includes a carrier and a long-range ordered Ni-Fe-Cu-M intermetallic compound, wherein M is selected from a VIB group metal element, an IVA group metal element or a VA group metal element. In the hydrogenation catalyst of the present invention, four metals, Ni, Fe, Cu and M, constitute a long-range ordered Ni-Fe-Cu-M intermetallic compound. The hydrogenation catalyst of the present invention is used for hydrogenating alkynes to prepare olefins, and can achieve efficient and highly selective hydrogenation under low temperature conditions, and has the advantages of high catalytic activity, good selectivity and good stability.

[0026] In the present invention, any type of M element that meets the above requirements can achieve the purpose of the present invention. According to a preferred embodiment of the present invention, M is selected from Cr, Sn, Ge, Sb or Bi. The use of the above metals is beneficial to improving the selectivity and stability of hydrogenating alkynes to olefins.

[0027] According to a preferred embodiment of the present invention, the hydrogenation catalyst of the present invention has characteristic diffraction peaks at 43.6±0.4°, 50.9±0.4° and 75.0±0.4°.

[0028] In the present invention, the lattice spacing in the hydrogenation catalyst Ni-Fe-Cu-M intermetallic compound is 0.206-0.216 nm.

[0029] In the present invention, the four metals in the hydrogenation catalyst of the present invention jointly constitute a Ni-Fe-Cu-M multi-dentate rhombus active site, and form a Ni-Fe-Cu-M quadruple site structure of electron-deficient Ni, electron-deficient Fe, electron-deficient Cu and isolated electron-rich M, which is beneficial to improving the selectivity and stability of hydrogenating alkynes to prepare olefins.

[0030] According to a preferred embodiment of the present invention, the crystal structure of the Ni-Fe-Cu-M intermetallic compound in the hydrogenation catalyst of the present invention is a body-centered cubic system, which is the most thermodynamically stable crystal structure; it is beneficial to improve the selectivity and stability of hydrogenation of alkynes to olefins.

[0031] In the present invention, the molar ratio of Ni to M in the hydrogenation catalyst can be selected in a wide range, which is illustrative but not limiting to the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to M is 1:0.95-1.05.

[0032] In the present invention, the molar ratio of Ni to Fe in the hydrogenation catalyst can be selected in a wide range, which is illustrative but not limiting to the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Fe is 1:0.95-1.05.

[0033] In the present invention, the molar ratio of Ni to Cu in the hydrogenation catalyst can be selected in a wide range, which is illustrative but not limiting to the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Cu is 1:0.95-1.05.

[0034] In the present invention, the types of carriers in the hydrogenation catalyst can be selected from a wide range, which is illustrative but not limiting to the scope of the present invention. For example, the carrier is a magnesium-aluminum metal mixed oxide; according to a preferred embodiment of the present invention, the carrier is selected from at least two of MgO, Al2O3 and MgAl2O4 carriers.

[0035] In the present invention, the molar ratio of Ni to Mg in the hydrogenation catalyst can be selected in a wide range, which is illustrative but not limiting to the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Mg is 1:14-18.

[0036] In the present invention, the molar ratio of Ni to Al in the hydrogenation catalyst can be selected in a wide range, which is illustrative but not limiting to the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Al is 1:3-5.

[0037] In the present invention, the content of the Ni-Fe-Cu-M intermetallic compound in the hydrogenation catalyst can be selected in a wide range. Based on the total weight of the hydrogenation catalyst, the mass content of the Ni-Fe-Cu-M intermetallic compound is 20-32wt%.

[0038] According to a preferred embodiment of the present invention, the mass content of the carrier is 68-80 wt % based on the total weight of the hydrogenation catalyst.

[0039] The present invention has no special requirements for the preparation method of the catalyst. The catalyst having the above characteristics can achieve the purpose of the present invention. The following exemplary description is not intended to limit the scope of the present invention. According to one embodiment of the present invention, the second aspect of the present invention provides a method for preparing a hydrogenation catalyst, which comprises:

[0040] The metal element of M and / or the metal salt of M are used with the Ni / Fe / Cu / Mg / Al five-element layered double hydroxide material to prepare the Ni / Fe / Cu / M / Mg / Al six-element layered double hydroxide material, and the Ni / Fe / Cu / M / Mg / Al six-element layered double hydroxide material is subjected to ion exchange with an alkaline solution and then reduced; wherein, M is selected from one of the metal elements of the VIB group, the metal elements of the IVA group or the metal elements of the VA group; the alkaline solution is selected from a solution containing carbonate ions or a solution containing bicarbonate ions. By the aforementioned method, the Ni / Fe / Cu / M / Mg / Al five-element layered double hydroxide material is prepared from the Ni / Fe / Cu / Mg / Al five-element layered double hydroxide material and subjected to ion exchange and reduction treatment to obtain a hydrogenation catalyst. In the present invention, the hydrogenation catalyst prepared by the aforementioned preparation method, Mg and Al form oxides or metal oxygenates as carriers, and the four metals Ni, Fe, Cu, and M jointly form a Ni-Fe-Cu-M intermetallic compound loaded on the carrier.

[0041] The hydrogenation catalyst prepared by the above preparation method of the present invention is used for hydrogenating alkynes to prepare olefins. It can achieve efficient and highly selective hydrogenation under low temperature conditions, avoids the formation of "green oil" to a great extent, and has the advantages of high catalytic activity, good selectivity and good stability.

[0042] In the present invention, the ion exchange introduces carbonate and / or bicarbonate ions to replace other anions (such as nitrate ions) to avoid the generation of substances that destroy the structure of the intermetallic compound formed by other anions. After the ion exchange, the carbonate / bicarbonate ions are reduced to generate CO2 gas, which is an inert gas and will not destroy the structure of the material, so that the hexavalent layered double hydroxide material is reduced to obtain a long-range ordered Ni-Fe-Cu-M intermetallic compound.

[0043] According to a preferred embodiment of the present invention, when M is selected from VIB group metal elements and IVA group metal elements, a metal salt solution containing M is contacted with a dispersion of a Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material and then separated to obtain a Ni / Fe / Cu / M / Mg / Al six-membered layered double hydroxide material; according to another preferred embodiment of the present invention, when M is selected from a VA group metal element, a metal single substance of M is ball-milled and mixed with a Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material to obtain a Ni / Fe / Cu / M / Mg / Al six-membered layered double hydroxide material; by the aforementioned method, metal M is introduced into the Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material by in-situ growth or ball milling to obtain a Ni / Fe / Cu / M / Mg / Al six-membered layered double hydroxide material; and an alkaline solution is used for ion exchange and reduction treatment to obtain a hydrogenation catalyst.

[0044] In the present invention, the amount of the metal element of M and / or the metal salt of M can be selected in a wide range. According to a preferred embodiment of the present invention, the amount of the metal element of M and / or the metal salt of M, calculated on an element basis, is such that the molar ratio of M to Ni is 1:0.95-1.05.

[0045] In the present invention, in the Ni / Fe / Cu / Mg / Al five-component layered double hydroxide material, the molar ratio of Ni to Fe can be selected in a wide range, which is illustrative but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Fe is 1:0.95-1.05.

[0046] In the present invention, in the Ni / Fe / Cu / Mg / Al five-component layered double hydroxide material, the molar ratio of Ni to Cu can be selected in a wide range, which is illustrative but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Cu is 1:0.95-1.05.

[0047] In the present invention, in the Ni / Fe / Cu / Mg / Al five-component layered double hydroxide material, the molar ratio of Ni to Mg can be selected in a wide range, which is illustrative but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Mg is 1:14-18.

[0048] In the present invention, in the Ni / Fe / Cu / Mg / Al five-component layered double hydroxide material, the molar ratio of Ni to Al can be selected in a wide range, which is illustrative but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Al is 1:3-5.

[0049] In the present invention, the concentration of anions in the alkaline solution can be selected in a wide range, which is for exemplary purposes only and does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the concentration of the anion solution is 0.05-0.3 mol / L.

[0050] In the present invention, the types of compounds providing anionic carbonate or bicarbonate in the alkaline solution can be selected from a wide range, which is exemplary, but does not limit the scope of the present invention. The compound providing anionic carbonate or bicarbonate is selected from one or more of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate. In the embodiments of the present invention, sodium carbonate is mainly used to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0051] In the present invention, when M is selected from VIB group metal elements and IVA group metal elements, the contact conditions are not particularly limited, and conventional conditions in the art are sufficient. This is an exemplary description, but it does not limit the scope of the present invention. According to one embodiment of the present invention, the contact conditions include: pH 9-11, temperature 60-70°C, and contact time can be determined according to actual needs. Preferably, the contact time is 14-18h.

[0052] In the present invention, when M is selected from VIB group metal elements and IVA group metal elements, the concentration range of the metal salt solution of M is relatively wide, which is for exemplary explanation, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, in the metal salt solution containing M, the concentration of the M element is 0.03-0.05 mol / L.

[0053] In the present invention, when M is selected from VIB group metal elements and IVA group metal elements, the method of separating and obtaining the Ni / Fe / Cu / M / Mg / Al hexavalent layered double hydroxide material is not particularly limited, and methods such as centrifugation, filtration, and suction filtration can all achieve the purpose of the present invention.

[0054] According to a specific embodiment of the present invention, the separated Ni / Fe / Cu / M / Mg / Al hexavalent layered double hydroxide material is washed and dried; for example, a solvent (deionized water, pure solvent, etc.) is used for washing until the washed solution is neutral; in the present invention, there is no particular limitation on the drying conditions, as long as the solvent can be removed, for example, drying at 40-130°C.

[0055] In the present invention, when M is selected from VA group metal elements, as long as the catalyst is in a uniform powder state, the ball milling conditions are not particularly limited, and conventional conditions in the art can be used. This is an exemplary description, but does not limit the scope of the present invention. According to one embodiment of the present invention, the ball milling conditions include: a rotation speed of 400-500 rpm; the time can be determined according to actual needs, preferably 1-1.5h.

[0056] In the present invention, as long as the Ni / Fe / Cu / M / Mg / Al hexavalent layered double hydroxide material is fully contacted with the alkaline solution, the ion exchange conditions are not particularly limited, and conventional conditions in the art are sufficient. This is an exemplary description, but it does not limit the scope of the present invention. According to one embodiment of the present invention, the ion exchange conditions include: a temperature of 30-60°C, and an exchange time that can be determined based on actual conditions, generally 8-36h.

[0057] In the present invention, the range of reduction conditions is relatively wide, as long as Mg and Al are not reduced to single substances; this is an exemplary description, but does not limit the scope of the present invention. According to one embodiment of the present invention, the reduction conditions include: a temperature of 800-1000°C; the reduction time can be determined according to actual needs, preferably, the reduction time is 3-5h.

[0058] According to one embodiment of the present invention, reduction is carried out in an atmosphere containing a reducing gas. The types of reducing gas can be selected from a wide range. This is for exemplary purposes only and does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the reducing gas is hydrogen. In practical applications, a mixture of hydrogen and inert gas is used.

[0059] In the present invention, the preparation method of the Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material is not particularly limited, and conventional technical means in the field can be used. According to a preferred embodiment of the present invention, the preparation method comprises co-precipitating a solution containing a Ni source, a Fe source, a Cu source, a Mg source and an Al source with a precipitant solution to obtain a dispersion of the Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material (which can be directly used to prepare the catalyst of the present invention), or separating and drying to obtain the Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material, and the precipitant solution is selected from a solution containing carbonate ions, a solution containing bicarbonate ions or ammonia water.

[0060] In the present invention, the molar ratio of the Ni source to the Fe source can be selected in a wide range, which is illustrative but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of each metal source, calculated as a metal element, to the Ni source is 1:0.95-1.05.

[0061] In the present invention, the molar ratio of the Ni source to the Cu source can be selected in a wide range, which is illustrative but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of each metal source, calculated as a metal element, to the Ni source is 1:0.95-1.05.

[0062] In the present invention, the molar ratio of the Ni source to the Mg source can be selected in a wide range, which is illustrative but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of each metal source, calculated as metal element, to the Ni source is 1:14-18.

[0063] In the present invention, the molar ratio of the Ni source to the Al source can be selected in a wide range, which is illustrative but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of each metal source, calculated as a metal element, to the Ni source is 1:3-5.

[0064] In the present invention, the optional range of Ni ion concentration in the solution containing Ni source, Fe source, Cu source, Mg source and Al source is relatively wide, which is illustrative but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the Ni ion concentration is 0.03-0.05 mol / L.

[0065] According to a preferred embodiment of the present invention, a solution containing a Ni source, a Fe source, a Cu source, a Mg source and an Al source is contacted with a precipitant solution, and a pH adjuster is added to adjust the pH to 9-11; preferably, the Ni source, the Fe source, the Cu source, the Mg source and the Al source are ultrasonically dispersed in ultrapure water to obtain a metal salt solution.

[0066] In the present invention, the contact conditions are not particularly limited, and the conventional conditions in the art can be used. This is an exemplary description, but it does not limit the scope of the present invention. According to one embodiment of the present invention, the contact conditions include: a temperature of 60-70°C; the present invention does not have any particular limitation on the contact time. According to the contact conditions of the present invention, a solution containing a Ni source, a Fe source, a Cu source, a Mg source and an Al source is contacted with a precipitant solution to obtain a Ni / Fe / Cu / Mg / Al five-element layered double hydroxide material.

[0067] In the present invention, the concentration of anions in the precipitant solution can be selected in a wide range, which is for exemplary purposes only and does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the concentration of anions in the precipitant is 0.1-1 mol / L.

[0068] In the present invention, the types of pH adjusters can be selected from a wide range, which is exemplary but not intended to limit the scope of the present invention. According to a preferred embodiment of the present invention, the pH adjuster is selected from one or more of NaOH, KOH or NaHCO3.

[0069] In the present invention, there is no particular limitation on the types of the Ni source, Fe source, Cu source, Mg source, M source and Al source, and they may be, for example, one or more of nitrates, sulfates and chlorides, preferably nitrates.

[0070] According to a preferred embodiment of the present invention, in step (1), a solution containing a Ni source, a Fe source, a Cu source, a Mg source and an Al source is added to the carbonate solution at a constant flow.

[0071] In the present invention, the flow rate of the solution containing Ni source, Fe source, Cu source, Mg source and Al source can be selected in a wide range, which is illustrative but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the flow rate is 0.7-1.1 mL / min.

[0072] In the present invention, the precipitant solution is in a flowing state during contact. For example, according to one embodiment of the present invention, it can be contacted with a solution containing a Ni source, a Fe source, a Cu source, a Mg source and an Al source at a rotation speed of 100-500 r / min, preferably 130-150 r / min.

[0073] The third aspect of the present invention provides a hydrogenation catalyst prepared by the preparation method of the present invention. The hydrogenation catalyst of the present invention comprises a carrier and a long-range ordered Ni-Fe-Cu-M intermetallic compound, wherein M is selected from a VIB group metal element, an IVA group metal element or a VA group metal element.

[0074] The hydrogenation catalyst prepared by the preparation method of the present invention has characteristic diffraction peaks at 2θ=43.6±0.4°, 50.9±0.4° and 75.0±0.4°.

[0075] In the hydrogenation catalyst prepared by the preparation method of the present invention, the lattice spacing of the Ni-Fe-Cu-M intermetallic compound is 0.206-0.216nm.

[0076] In the hydrogenation catalyst prepared by the preparation method of the present invention, the four metals together form a Ni-Fe-Cu-M multi-tooth rhombus active site, and form a Ni-Fe-Cu-M quadruple site structure of electron-deficient Ni, electron-deficient Fe, electron-deficient Cu and isolated electron-rich M.

[0077] In the hydrogenation catalyst prepared by the preparation method of the present invention, the crystal structure of the Ni-Fe-Cu-M intermetallic compound is a body-centered cubic system.

[0078] In the hydrogenation catalyst prepared by the preparation method of the present invention, the molar ratio of Ni to M can be selected in a wide range, which is illustrative but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to M is 1:0.95-1.05.

[0079] In the hydrogenation catalyst prepared by the preparation method of the present invention, the molar ratio of Ni to Fe can be selected in a wide range, which is illustrative but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Fe is 1:0.95-1.05.

[0080] In the hydrogenation catalyst prepared by the preparation method of the present invention, the molar ratio of Ni to Cu can be selected in a wide range, which is illustrative but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the molar ratio of Ni to Cu is 1:0.95-1.05.

[0081] In the hydrogenation catalyst prepared by the preparation method described in the present invention, the type of carrier can be selected from a wide range, which is illustrative but not limiting the scope of the present invention. For example, the carrier is a magnesium-aluminum metal mixed oxide; according to a preferred embodiment of the present invention, the carrier is selected from at least two of MgO, Al2O3 and MgAl2O4 carriers.

[0082] In the hydrogenation catalyst prepared by the preparation method of the present invention, the content of the Ni-Fe-Cu-M intermetallic compound can be selected in a wide range. Based on the total weight of the hydrogenation catalyst, the mass content of the Ni-Fe-Cu-M intermetallic compound is 20-32wt%.

[0083] In the hydrogenation catalyst prepared by the preparation method of the present invention, the mass content of the carrier is 68-80wt% based on the total weight of the hydrogenation catalyst.

[0084] The fourth aspect of the present invention provides an application of the hydrogenation catalyst of the present invention in the preparation of olefins by hydrogenation of alkynes. The hydrogenation catalyst of the present invention has the advantages of high catalytic activity, good selectivity and good stability when applied to the preparation of olefins by hydrogenation of alkynes.

[0085] According to a preferred embodiment of the present invention, a method for applying a hydrogenation catalyst to hydrogenate alkynes to prepare olefins comprises: subjecting a feed gas containing alkynes to a hydrogenation reaction in the presence of a catalyst; the catalyst comprises the hydrogenation catalyst of the present invention.

[0086] In the present invention, the volume ratio of alkyne to hydrogen can be selected in a wide range, which is illustrative but not limiting to the scope of the present invention. According to a preferred embodiment of the present invention, the volume ratio is 1:5-100.

[0087] In the present invention, the concentration of alkyne in the alkyne-containing feed gas can be selected in a wide range, which is illustrative but not limiting. According to a preferred embodiment of the present invention, the concentration of alkyne is 0.5-1.0% by volume.

[0088] In the present invention, the concentration range of olefins having the same number of carbon atoms as the alkyne in the alkyne-containing feed gas is relatively wide, which is for exemplary purposes only, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the concentration of olefins having the same number of carbon atoms as the alkyne is 5-60% by volume.

[0089] In the present invention, the source of the raw gas containing alkynes can be selected from a wide range. According to a preferred embodiment of the present invention, the raw gas containing alkynes comes from petroleum fraction cracking gas.

[0090] In the present invention, the gas phase space velocity of the hydrogenation reaction can be selected in a wide range, which is exemplary but not limiting the scope of the present invention. According to a preferred embodiment of the present invention, the gas phase space velocity is 4000-4600h -1 .

[0091] In the present invention, the hydrogenation conditions are not particularly limited, and the conventional conditions in the art are sufficient. This is for exemplary explanation, but does not limit the scope of the present invention. According to one embodiment of the present invention, the hydrogenation conditions include: temperature of 20-130° C.; pressure of 0.1-0.2 MPa.

[0092] According to a preferred embodiment of the present invention, the alkyne is selected from C2-C6 alkynes, preferably acetylene and / or propyne.

[0093] The hydrogenation catalyst of the present invention is particularly suitable for hydrogenation of crude ethylene vapor produced by cracking of petroleum fractions. According to a preferred embodiment of the present invention, the crude ethylene vapor produced by cracking of petroleum fractions contains 0.5-1.0% by volume of acetylene and 20-100% by volume of ethylene.

[0094] The hydrogenation catalyst of the present invention is particularly suitable for hydrogenation of crude propylene vapor produced by cracking of petroleum fractions. According to a preferred embodiment of the present invention, the crude propylene vapor produced by cracking of petroleum fractions contains 0.5-2.0% by volume of propyne and 5-100% by volume of propylene.

[0095] In the context of the present invention, the XRD test conditions are as follows: the structure of the reduced catalyst was characterized using a D / MAX-2500 X-ray diffractometer manufactured by Rigaku Corporation of Japan. Cu-Ka radiation (λ=0.15406nm) was used, the operating current was 100mA, the voltage was 40kV, the scanning range was 2θ=20-80°, and the scanning rate was 5° / min.

[0096] Transmission electron microscope test conditions and instrument model: Use the JEM-2010F high-resolution TEM manufactured by Japan's JEOL company, which is equipped with a LaB6 electron gun, an adjustable acceleration voltage of 80-200kV, a point resolution of ≤0.23nm, a line resolution of 0.14nm, a minimum beam spot size of better than 20nm, and a magnification of 500,000-1.5 million times that is continuously adjustable. The relevant test details are: take a small amount of the powder to be tested and disperse it in anhydrous ethanol, then perform ultrasonic treatment until the suspension is uniformly transparent, use a 10μL pipette to transfer a drop of the suspension onto an ordinary carbon film, quickly dry it under an infrared lamp, place the resulting sample on the sample gun, and finally transfer it to the sample chamber for analysis and characterization.

[0097] High-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) test conditions and instrument model: The JEM-2010F high-resolution TEM manufactured by Japan's JEOL company was also used, and the sample preparation method was the same as that of the transmission electron microscope.

[0098] Spherical aberration electron microscope test conditions and instrument model: Use Jifeng Electronics HF5000 produced by Hitachi (HITACHI) of Japan, with an acceleration voltage of 200kV, STEM resolution: 0.078nm, TEM resolution: 0.078nm, equipped with X-ray energy spectrum analyzer and electron energy loss spectrometer.

[0099] Catalyst performance evaluation: carried out on the ZKJC-RJ-X system of Beijing Wanlonghe Technology Co., Ltd., including:

[0100] The components in the reactants and products were analyzed online using a 4-channel microchromatograph Micro GC3000 (INFICON, USA). Hydrogen and nitrogen were analyzed using molecular sieve columns, alkynes were analyzed using Plot-U columns, alkenes and alkanes were analyzed using alumina columns, trace carbon 4 components contained in the feed gas were analyzed using an OV-1 capillary column, the detector used a thermal conductivity detector (TCD), and the chromatographic carrier gas was argon (Ar) and helium (He).

[0101] Evaluation conditions for preparing ethylene from acetylene: total inlet gas flow rate is 100 sccm (Standard Cubic Centimeter Per Minute), the raw gas composition is 0.5% acetylene, 50.0% ethylene, 10.0% hydrogen, and the remaining gas is nitrogen, at normal pressure, the reaction temperature is 20-130°C, and the catalyst loading is 100 mg.

[0102] Evaluation conditions for preparing propylene from propyne: total inlet gas flow rate is 100 sccm, the raw gas is 1.0% propyne, 10.0% propylene, 5.0% hydrogen by volume, and the remaining gas is nitrogen; under normal pressure conditions, the reaction temperature is 110°C; the catalyst loading is 100 mg.

[0103] Weigh 100 mg of catalyst sample, mix it evenly with 10 times the mass of quartz sand, and then fill it in the constant temperature zone of the stainless steel reaction tube. After the catalyst is filled, first check the reaction system for leaks, and introduce a certain pressure of N2 (such as 10 bar) into the reaction system. If the pressure remains unchanged, it means that the reaction system is well sealed and the evaluation experiment can be carried out. Set the nitrogen flow rate to 20sccm, raise the temperature to the reduction temperature and turn off the nitrogen, and set the hydrogen flow rate to 20sccm. After a certain period of reduction, turn off the hydrogen; set the nitrogen flow rate to 20sccm until the temperature drops to the reaction temperature, and then set the pressure required for the reaction. When the reaction conditions are stable, set the flow rate of each reaction component and cut the furnace six-way valve to bypass, so that the mixed reaction gas directly enters the chromatograph to detect the concentration of each component before the reaction. After the chromatographic results are stable, cut the furnace six-way valve back, the mixed components enter the reaction tube to start the reaction, and the gas at the outlet of the reaction tube enters the online chromatograph for detection.

[0104] The calculation formulas for acetylene conversion C (C2H2), ethylene selectivity S (C2H4) and ethylene yield Y (C2H4) are:

[0105]

[0106]

[0107] Y(C2H4)=C(C2H2)×S(C2H4)

[0108] The calculation formulas for propyne conversion C (C3H4), propylene selectivity S (C3H6) and propylene yield Y (C2H6) are:

[0109]

[0110]

[0111] Y(C3H6)=C(C3H4)×S(C3H6)

[0112] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0113] Example 1

[0114] according to Figure 1 The flow chart shown is for preparing Ni-Fe-Cu-Sn hydrogenation catalyst

[0115] (1) According to the molar ratio of Ni to Fe being 1:1, the molar ratio of Ni to Cu being 1:1, the molar ratio of Ni to Mg being 1:16, and the molar ratio of Ni to Al being 1:4, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, Fe(NO3)3·9H2O, Mg(NO3)2·6H2O, and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water and ultrasonically dispersed to obtain a mixed metal salt solution, wherein the Ni ion concentration in the solution was 0.033 mol / L;

[0116] 100 mL of 0.4 mol / L sodium carbonate aqueous solution was used as a precipitant, the precipitant was heated to 65° C., and the rotation speed was controlled to 140 r / min. A mixed metal salt solution was pumped into the precipitant at a constant flow of 0.8 mL / min, and a 2.5 mol / L NaOH solution was added to adjust the pH of the reaction system to 10 for co-precipitation to obtain a dispersion of Ni / Fe / Cu / Mg / Al five-element layered double hydroxide material.

[0117] (2) Maintaining the temperature at 65°C, 30 mL of 0.11 mol / L tin chloride aqueous solution was pumped into the dispersion obtained in step (1) at a constant flow of 0.8 mL / min, and 2.5 mol / L NaOH solution was added to adjust the pH of the reaction system to 10 until the feeding was completed, and stirred for 16 h; then vacuum filtered, washed with deionized water until the pH of the washing liquid was neutral, and dried at 110°C for 16 h to obtain a solid; the solid was ion exchanged with 200 mL of 0.1 mol / L Na2CO3 solution at a temperature of 35°C for 12 h to obtain a green block solid Ni / Fe / Cu / Sn / Mg / Al hexalayered double hydroxide material X9.

[0118] (3) The Ni / Fe / Cu / Sn / Mg / Al hexavalent layered double hydroxide material X9 obtained in step (2) was reduced at 900° C. in a H2 / N2 atmosphere (volume ratio 1:4) for 4 h to obtain a Ni-Fe-Cu-Sn hydrogenation catalyst, denoted as X9-900. The mass content of the carrier in the catalyst was 74.09%; the mass content of the Ni-Fe-Cu-Sn intermetallic compound was 25.91%.

[0119] Figure 2 b is the XRD spectrum of the hydrogenation catalyst X9-900 prepared in Example 1, and diffraction peaks of different intensities appear at 43.2°, 50.5° and 74.6°, which correspond to the diffraction peaks of the (111), (200) and (220) planes of the cubic Ni-Fe-Cu-Sn intermetallic compound, respectively. From the results, it can be seen that the crystal form of the Ni-Fe-Cu-Sn intermetallic compound is the most thermodynamically stable body-centered cubic system, the diffraction intensity of the (111) crystal plane is the highest, and its distribution on the surface of the intermetallic compound particles accounts for the largest proportion.

[0120] The microstructure of X9-900 was observed by transmission electron microscopy. Figure 3 As shown, it can be seen that the hydrogenation catalyst of the present invention has obvious lattice fringes, and the measured lattice spacing is 0.216nm, corresponding to the (111) crystal plane of the Ni-Fe-Cu-Sn intermetallic compound, which further verifies Figure 2 b XRD results, i.e., the Ni-Fe-Cu-Sn intermetallic compound particles are uniformly distributed on the oxide support, and the most exposed crystal plane is the (111) crystal plane.

[0121] like Figure 4As shown, further elemental analysis of X9-900 revealed that the elements Ni, Fe, Cu, and Sn were evenly distributed, among which Mg and Al elements corresponded to MgO and MgAl2O4 carriers, indicating that the Ni-Fe-Cu-Sn intermetallic compound nanoparticles were evenly dispersed and anchored on the MgO and MgAl2O4 mixed oxide carriers. Figure 5 a is a high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) image of catalyst X9-900, Figure 5 b is the line scan element analysis diagram of the selected nanoparticles in the corresponding HAADF-STEM image. According to the corresponding EDS line scan analysis diagram, it can be found that the elements Ni, Fe, Cu, and Sn in the Ni-Fe-Cu-Sn intermetallic compound catalyst are evenly distributed, and the content ratio of the elements Ni, Fe, Cu, and Sn is 1:1:1:1. This result is consistent with Figure 4 Consistent.

[0122] The results are as follows: Figure 6 As shown, Figure 6 The lattice spacing along the arrow direction in a is 0.215 nm, corresponding to the (111) crystal plane of the Ni-Fe-Cu-Sn intermetallic compound shown in 6b. It should be noted that, compared with the Ni3Sn in Comparative Example 1, after the guest metals Fe and Cu in Example 1 directional replace part of the Ni sites in the parent alloy Ni3Sn, the high-temperature hydrogen heat treatment can cause the crystal phase to transform into a thermodynamically more stable body-centered cubic Ni-Fe-Cu-Sn intermetallic compound, thereby exposing the (111) crystal plane; Figure 6 c is along Figure 6 The intensity distribution of the atomic image shown by the arrow in a, combined with Figure 6 d further shows that the atomic arrangement of the catalyst particles is highly consistent with the simulated atomic arrangement of the Ni-Fe-Cu-Sn intermetallic compound calculated by density functional theory, indicating that the sites of the four metal elements are arranged in order, verifying the long-range order of the Ni-Fe-Cu-Sn intermetallic compound, and that the four metals together constitute the Ni-Fe-Cu-Sn multi-toothed rhombus active sites, and form a quadruple site structure of Ni-Fe-Cu-Sn with electron-deficient Ni, electron-deficient Fe, electron-deficient Cu and isolated electron-rich Sn.

[0123] like Figure 7As shown, the pyrolysis GC-MS results of the Ni-Fe-Cu-Sn intermetallic compound hydrogenation catalyst prepared in Example 1 and the Ni3Sn hydrogenation catalyst of Comparative Example 1 and standard samples composed of different linear hydrocarbon compounds are shown. The intensity of the green oil decomposition peak of the Ni3Sn hydrogenation catalyst of Comparative Example 1 after 24 hours of reaction is significantly stronger than that of the Ni-Fe-Cu-Sn intermetallic compound hydrogenation catalyst after 24 hours of reaction, which indicates that: compared with the Ni-Fe-Cu-Sn intermetallic compound hydrogenation catalyst of Example 1, more green oil is formed and accumulated on the Ni3Sn hydrogenation catalyst of Comparative Example 1 during the hydrogenation process.

[0124] The X9-900 catalyst was applied to acetylene hydrogenation, and the stability of the catalyst was evaluated at 110°C: the acetylene conversion and ethylene selectivity at different reaction times are shown in Table 1.

[0125] Table 1

[0126]

[0127]

[0128] The results showed that after 48 hours of reaction, the acetylene conversion rate of the X9-900 catalyst was still maintained at more than 97%, and the ethylene selectivity was maintained at more than 97%. It can be seen that the ethylene yield was maintained at more than 94%, indicating that it has good stability.

[0129] The X9-900 catalyst was applied to propyne hydrogenation, and the stability of the catalyst was evaluated at 110°C: the propyne conversion and propylene selectivity at different reaction times are shown in Table 2.

[0130] Table 2

[0131]

[0132]

[0133] The results show that after 48 hours of reaction, the propyne conversion rate of the X9-900 catalyst prepared in Example 1 is still maintained at more than 97%, the propylene selectivity is maintained at more than 97%, and the propylene yield is maintained at more than 95%, indicating that it has good stability.

[0134] The X9-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: the ethylene selectivity and ethylene yield at 48h of reaction are shown in Tables 3 and 4.

[0135] Example 2

[0136] The implementation process is the same as that of Example 1, except that the tin chloride solution is replaced by a 0.11 mol / L chromium chloride aqueous solution obtained by dissolving 0.89 g CrCl3·6H2O in 30 mL ultrapure water and ultrasonically dispersing the solution. The prepared catalyst is designated as X10-900. The mass content of the carrier in the catalyst is 78.68%; the mass content of the Ni-Fe-Cu-Cr intermetallic compound is 21.32%.

[0137] The XRD patterns of the catalysts are shown in Figure 8 As shown, characteristic diffraction peaks appear at 2θ=43.9°, 51.2° and 75.4°, indicating that the catalyst contains Ni-Fe-Cu-Cr intermetallic compounds, and the crystal form is the most thermodynamically stable body-centered cubic system;

[0138] Spherical aberration electron microscopy images of the catalyst Figure 6 Similarly, the lattice spacing of the Ni-Fe-Cu-Cr intermetallic compound is 0.206 nm, the Ni-Fe-Cu-Cr intermetallic compound has a long-range order, and the four metals together constitute the Ni-Fe-Cu-Cr multi-tooth rhombus active sites, forming a Ni-Fe-Cu-Cr quadruple site structure of Ni, Fe, Cu and isolated Cr.

[0139] Catalyst element analysis chart and Figure 4 Similarly, the elements Ni, Fe, Cu, and Cr are evenly distributed, where Mg and Al elements correspond to MgO and MgAl2O4 supports, indicating that the Ni-Fe-Cu-Cr intermetallic compound nanoparticles are uniformly dispersed and anchored on the MgO and MgAl2O4 mixed oxide supports.

[0140] The X10-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0141] Example 3

[0142] The implementation process is the same as Example 1, except that the tin chloride solution is replaced by a 0.11 mol / L ammonium hexafluorogermanate solution obtained by dissolving 0.75 g (NH4)2GeF6 in 30 mL ultrapure water and ultrasonically dispersing the solution. The prepared catalyst is designated as X11-900. The mass content of the carrier in the catalyst is 77.20%; the mass content of the Ni-Fe-Cu-Ge intermetallic compound is 22.80%.

[0143] The XRD patterns of the catalysts are shown in Figure 8 As shown, characteristic diffraction peaks appear at 2θ=43.9°, 51.1° and 75.4°, indicating that the catalyst contains Ni-Fe-Cu-Ge intermetallic compounds, and the crystal form is the most thermodynamically stable body-centered cubic system;

[0144] Spherical aberration electron microscopy images of the catalyst Figure 6 Similarly, the lattice spacing of the Ni-Fe-Cu-Ge intermetallic compound is 0.207 nm, the Ni-Fe-Cu-Ge intermetallic compound has a long-range order, and the four metals together constitute the Ni-Fe-Cu-Ge multi-tooth rhombus active sites, forming a Ni-Fe-Cu-Ge quadruple site structure of Ni, Fe, Cu and isolated Ge.

[0145] Catalyst element analysis chart and Figure 4 Similarly, the elements Ni, Fe, Cu, and Ge are evenly distributed, where Mg and Al elements correspond to MgO and MgAl2O4 supports, indicating that the Ni-Fe-Cu-Ge intermetallic compound nanoparticles are uniformly dispersed and anchored on the MgO and MgAl2O4 mixed oxide supports.

[0146] The X11-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: the acetylene conversion, ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0147] Example 4

[0148] (1) According to the molar ratio of Ni to Fe being 1:1, the molar ratio of Ni to Cu being 1:1, the molar ratio of Ni to Mg being 1:16, and the molar ratio of Ni to Al being 1:4, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, Fe(NO3)3·9H2O, Mg(NO3)2·6H2O, and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water and ultrasonically dispersed to obtain a mixed metal salt solution, wherein the Ni ion concentration in the solution was 0.033 mol / L;

[0149] 100 mL of 0.4 mol / L sodium carbonate aqueous solution was used as a precipitant, the precipitant was heated to 65°C, and the rotation speed was controlled to 140 r / min, a mixed metal salt solution was pumped into the precipitant at a constant flow of 0.8 mL / min, and a 2.5 mol / L NaOH solution was added to adjust the pH of the reaction system to 10 for co-precipitation to obtain a dispersion of Ni / Fe / Cu / Mg / Al five-element layered double hydroxide material.

[0150] (2) The dispersion containing the Ni / Fe / Cu / Mg / Al five-element layered double hydroxide material obtained in step (1) was stirred for 16 h while maintaining the temperature at 65° C., then vacuum filtered, washed with deionized water until the pH of the washing liquid was neutral, and dried at 110° C. for 16 h to obtain a solid. The obtained solid was mechanically ground with 0.41 g of antimony powder at 400 rpm for 1.5 h and mixed evenly, and then ion exchanged with 200 mL of 0.05 mol / L NaHCO3 solution at a temperature of 55° C. for 8 h to obtain a gray block solid Ni / Fe / Cu / Sb / Mg / Al six-element layered double hydroxide material X12.

[0151] (3) The Ni / Fe / Cu / Sb / Mg / Al hexavalent layered double hydroxide material X12 obtained in step (2) was reduced at 900° C. in a H2 / N2 atmosphere (volume ratio 1:4) for 4 h to obtain a Ni-Fe-Cu-Sb hydrogenation catalyst, denoted as X12-900. The mass content of the carrier in the catalyst was 73.90%; the mass content of the Ni-Fe-Cu-Sb intermetallic compound was 26.10%.

[0152] The XRD patterns of the catalysts are shown in Figure 8 As shown, characteristic diffraction peaks appear at 2θ=44.0°, 51.1° and 75.3°, indicating that the catalyst contains Ni-Fe-Cu-Sb intermetallic compounds, and the crystal form is the most thermodynamically stable body-centered cubic system;

[0153] Spherical aberration electron microscopy images of the catalyst Figure 6 Similarly, the lattice spacing of the Ni-Fe-Cu-Sb intermetallic compound is 0.210 nm, the Ni-Fe-Cu-Sb intermetallic compound has a long-range order, and the four metals together constitute the Ni-Fe-Cu-Sb multi-tooth rhombus active sites, forming a Ni-Fe-Cu-Sb quadruple site structure of Ni, Fe, Cu and isolated Sb.

[0154] Catalyst element analysis chart and Figure 4 Similarly, the elements Ni, Fe, Cu, and Sb are evenly distributed, where Mg and Al elements correspond to MgO and MgAl2O4 supports, indicating that the Ni-Fe-Cu-Sb intermetallic compound nanoparticles are uniformly dispersed and anchored on the MgO and MgAl2O4 mixed oxide supports.

[0155] The X12-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0156] Example 5

[0157] The implementation process is the same as that of Example 4, except that 0.41 g of antimony powder is replaced by 0.70 g of bismuth powder. The prepared catalyst is recorded as X13-900. The mass content of the carrier in the catalyst is 72.62%; the mass content of the Ni-Fe-Cu-Bi intermetallic compound is 27.38%.

[0158] The XRD patterns of the catalysts are shown in Figure 8 As shown, characteristic diffraction peaks appear at 2θ=43.4°, 50.7° and 74.6°, indicating that the catalyst contains Ni-Fe-Cu-Bi intermetallic compounds, and the crystal form is the most thermodynamically stable body-centered cubic system;

[0159] Spherical aberration electron microscopy images of the catalyst Figure 6 Similarly, the lattice spacing of the Ni-Fe-Cu-Bi intermetallic compound is 0.212 nm, the Ni-Fe-Cu-Bi intermetallic compound has a long-range order, and the four metals together constitute the Ni-Fe-Cu-Bi multi-tooth rhombus active sites, forming a Ni-Fe-Cu-Bi quadruple site structure of Ni, Fe, Cu and isolated Bi.

[0160] Catalyst element analysis chart and Figure 4 Similarly, the elements Ni, Fe, Cu, and Bi are evenly distributed, where Mg and Al elements correspond to MgO and MgAl2O4 supports, indicating that the Ni-Fe-Cu-Bi intermetallic compound nanoparticles are uniformly dispersed and anchored on the MgO and MgAl2O4 mixed oxide supports.

[0161] The X13-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0162] Comparative Example 1

[0163] (1) According to the molar ratio of Ni to Mg being 1:5 and the molar ratio of Ni to Al being 1:1.7, Ni(NO3)2·6H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 70 mL of ultrapure water by ultrasonic dispersion to obtain a mixed metal salt solution, wherein the Ni ion concentration in the solution was 0.14 mol / L;

[0164] 100 mL of 0.4 mol / L sodium carbonate aqueous solution was used as a precipitant, the precipitant was heated to 65°C, and the rotation speed was controlled to 140 r / min, a mixed metal salt solution was pumped into the precipitant at a constant flow of 0.8 mL / min, and a 2.5 mol / L NaOH solution was added to adjust the pH of the reaction system to 10 for co-precipitation to obtain a dispersion containing a Ni / Mg / Al ternary layered double hydroxide material.

[0165] (2) Maintaining the temperature at 65°C, 30 mL of 0.11 mol / L tin chloride aqueous solution was pumped into the dispersion obtained in step (1) at a constant flow of 0.8 mL / min, and 2.5 mol / L NaOH solution was added to adjust the pH of the reaction system to 10 until the feeding was completed, and stirred for 16 h; then vacuum filtered, washed multiple times until the pH of the washing liquid was neutral, dried at 110°C for 16 h to obtain a solid, and further ion exchanged in 0.1 mol / L Na2CO3 solution at a temperature of 35°C for 12 h to obtain a green block solid Ni / Sn / Mg / Al quaternary layered double hydroxide material X1.

[0166] (3) The Ni / Sn / Mg / Al quaternary layered double hydroxide material X1 obtained in step (2) was reduced at 900° C. in a H2 / N2 atmosphere (volume ratio 1:4) for 4 h to obtain a Ni3Sn binary intermetallic compound catalyst, denoted as X1-900. The mass content of the carrier in the catalyst was 25.43%; the mass content of the Ni3Sn intermetallic compound was 74.57%.

[0167] Figure 2 a is the XRD spectrum of hydrogenation catalyst X1-900, with obvious diffraction peaks at 19.4°, 28.7°, 39.3°, 45.0°, and 59.3°, which can be respectively attributed to the diffraction peaks of (100), (101), (200), (201), and (202) planes of the standard card of the oblique hexagonal Ni3Sn binary intermetallic compound (JCPDS No.64-6749). By comparing with Comparative Example 1, it is further verified that the crystal form of the Ni-Fe-Cu-Sn medium entropy metal compound in Example 1 is significantly transformed compared with the Ni3Sn binary intermetallic compound, and is transformed into the most thermodynamically stable body-centered cubic system. The diffraction intensity of the (111) crystal plane is the highest, and its distribution on the surface of the medium entropy metal particles accounts for the largest proportion. The lattice spacing is 0.214nm.

[0168] The X1-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0169] Comparative Example 2

[0170] The implementation process is the same as that of Comparative Example 1, except that the aqueous tin chloride solution is substituted for 30 mL of 0.11 mol / L chromium chloride solution. The prepared catalyst is recorded as X2-900. The mass content of the carrier in the catalyst is 20.87%; the mass content of the Ni3Cr intermetallic compound is 79.13%.

[0171] The lattice spacing is 0.203nm.

[0172] The X2-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0173] Comparative Example 3

[0174] The implementation process is the same as that of Comparative Example 1, except that the tin chloride solution is replaced by 30 mL of 0.11 mol / L ammonium hexafluorogermanate solution. The prepared catalyst is recorded as X3-900. The mass content of the carrier in the catalyst is 22.34%; the mass content of the Ni3Ge intermetallic compound is 77.66%.

[0175] The lattice spacing is 0.203nm.

[0176] The X3-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0177] Comparative Example 4

[0178] (1) According to the molar ratio of Ni to Mg being 1:5 and the molar ratio of Ni to Al being 1:1.7, Ni(NO3)2·6H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 70 mL of ultrapure water by ultrasonic dispersion to obtain a mixed metal salt solution, wherein the Ni ion concentration in the solution was 0.14 mol / L;

[0179] 100 mL of 0.4 mol / L sodium carbonate aqueous solution was used as a precipitant, the precipitant was heated to 65°C, and the rotation speed was controlled to 140 r / min, a mixed metal salt solution was pumped into the precipitant at a constant flow of 0.8 mL / min, and a 2.5 mol / L NaOH solution was added to adjust the pH of the reaction system to 10 for co-precipitation to obtain a dispersion containing a Ni / Mg / Al ternary layered double hydroxide material.

[0180] (2) The dispersion containing the Ni / Mg / Al ternary layered double hydroxide material obtained in step (1) was stirred for 16 h while maintaining the temperature at 65° C., then vacuum filtered, washed with deionized water until the pH of the washing liquid was neutral, and dried at 110° C. for 16 h to obtain a solid. The obtained solid was mechanically ground with 0.41 g of antimony powder at 400 rpm for 1.5 h and mixed evenly, and then ion exchanged in a 0.1 mol / L Na2CO3 solution at a temperature of 35° C. for 12 h to obtain a gray block solid Ni / Sb / Mg / Al quaternary layered double hydroxide material X4.

[0181] (3) The Ni / Sb / Mg / Al hexavalent layered double hydroxide material X4 obtained in step (2) was reduced at 900° C. in a H2 / N2 atmosphere (volume ratio 1:4) for 4 h to obtain a Ni-Fe-Cu-Sb hydrogenation catalyst, denoted as X4-900. The mass content of the carrier in the catalyst was 25.62%; the mass content of the Ni3Sb intermetallic compound was 74.38%.

[0182] The lattice spacing is 0.207nm.

[0183] The X4-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0184] Comparative Example 5

[0185] The implementation process is the same as that of Comparative Example 4, except that 0.41 g of antimony powder is replaced by 0.70 g of bismuth powder. The prepared catalyst is recorded as X5-900. The mass content of the carrier in the catalyst is 30.81%; the mass content of the Ni3Bi intermetallic compound is 69.19%.

[0186] The lattice spacing is 0.208nm.

[0187] The X5-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0188] Comparative Example 6

[0189] The implementation process is the same as Example 1, except that after drying at 110° C. for 16 h to obtain a solid in step (2), ion exchange is not performed and step (3) is directly performed; the prepared hydrogenation catalyst is recorded as X6-900.

[0190] The X6-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0191] Comparative Example 7

[0192] The implementation process is the same as Example 4, except that after mechanical grinding in step (2), ion exchange is not performed and step (3) is performed directly; the prepared hydrogenation catalyst is recorded as X7-900.

[0193] The X7-900 catalyst was applied to acetylene hydrogenation, and the catalyst was evaluated at different temperatures: ethylene selectivity and ethylene yield are shown in Tables 3 and 4.

[0194] Comparative Example 8

[0195] (1) According to the molar ratio of Ni to Fe being 1:1, the molar ratio of Ni to Cu being 1:1, the molar ratio of Ni to Mg being 1:16, the molar ratio of Ni to Al being 1:4, and the molar ratio of Ni to Sn being 1:1, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, Fe(NO3)3·9H2O, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and tin chloride were dissolved in 100 mL of ultrapure water. The solution underwent a hydrolysis reaction and a flocculent precipitate appeared, and co-precipitation could not be performed.

[0196] Table 3 Ethylene selectivity (%)

[0197]

[0198] Table 4 Ethylene yield (%)

[0199]

[0200]

[0201] In Table 3 and Table 4, negative values ​​of selectivity and yield indicate that ethylene in the raw material is hydrogenated to produce ethane. Combining the results of Table 3 and Table 4, it can be seen that when the reaction pressure is normal pressure and the raw material is rich in ethylene, the Ni-Fe-Cu-M hydrogenation catalyst of the present invention has significantly improved ethylene selectivity and yield compared to the binary Ni-based catalyst. In the range of 70-130°C, the Ni-Fe-Cu-M hydrogenation catalyst prepared in the embodiment has extremely high ethylene selectivity, and when the temperature reaches 100°C and above, a higher acetylene conversion rate and ethylene selectivity can be obtained at the same time. It is explained that the Ni-Fe-Cu-M hydrogenation catalyst prepared by the technical solution of the present invention can significantly improve the acetylene conversion rate, ethylene selectivity and yield of the binary Ni-based catalyst.

[0202] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A hydrogenation catalyst, characterized in that The hydrogenation catalyst comprises a magnesium-aluminum carrier and a long-range ordered Ni-Fe-Cu-M intermetallic compound, wherein M is selected from a VIB group metal element, an IVA group metal element or a VA group metal element.

2. The catalyst according to claim 1, wherein M is selected from Cr, Sn, Ge, Sb or Bi; and / or The hydrogenation catalyst has characteristic diffraction peaks at 2θ=43.6±0.4°, 50.9±0.4° and 75.0±0.4°; and / or The lattice spacing of the Ni-Fe-Cu-M intermetallic compound is 0.206-0.216 nm; and / or In the hydrogenation catalyst, the four metals together constitute a Ni-Fe-Cu-M multi-toothed rhombus active site, and form a Ni-Fe-Cu-M quartet site structure of electron-deficient Ni, electron-deficient Fe, electron-deficient Cu and isolated electron-rich M; and / or The crystal structure of the Ni-Fe-Cu-M intermetallic compound is a body-centered cubic system.

3. The catalyst according to claim 1 or 2, wherein The molar ratio of Ni to M is 1:0.95-1.05; and / or The molar ratio of Ni to Fe is 1:0.95-1.05; and / or The molar ratio of Ni to Cu is 1:0.95-1.05; and / or The magnesium aluminum carrier is a magnesium aluminum metal mixed oxide, preferably at least two of MgO, Al2O3 and MgAl2O4; and / or The molar ratio of Ni to Mg is 1:14-18; and / or The molar ratio of Ni to Al is 1:3-5; and / or The mass content of the carrier is 68-80wt% based on the total weight of the hydrogenation catalyst; and / or The mass content of Ni-Fe-Cu-M intermetallic compound is 20-32wt%.

4. A method for preparing a hydrogenation catalyst, characterized in that: The method includes: Prepare Ni / Fe / Cu / M / Mg / Al hexalayered double hydroxide material by reacting a metal element of M or a metal salt of M with a Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material, and perform ion exchange on the Ni / Fe / Cu / M / Mg / Al hexalayered double hydroxide material and an alkaline solution before reduction; Wherein, M is selected from one of the metal elements of Group VIB, Group IVA or Group VA; The alkaline solution is selected from a solution containing carbonate ions and / or a solution containing bicarbonate ions.

5. The preparation method according to claim 4, wherein: When M is selected from a VIB group metal element or an IVA group metal element, a metal salt solution containing M is contacted with a dispersion of a Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material and then separated to obtain a Ni / Fe / Cu / M / Mg / Al six-membered layered double hydroxide material; or When M is selected from Group VA metal elements, the metal element of M and the Ni / Fe / Cu / Mg / Al five-membered layered double hydroxide material are ball-milled to obtain the Ni / Fe / Cu / M / Mg / Al six-membered layered double hydroxide material.

6. The preparation method according to claim 4 or 5, wherein: Calculated as an element, the metal element of M or the metal salt of M is such that the molar ratio of M to Ni is 1:0.95-1.05; and / or The concentration of anions in the alkaline solution is 0.05-0.3 mol / L; and / or The compound providing anionic carbonate and / or bicarbonate in the alkaline solution is selected from one or more of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate; and / or In the Ni / Fe / Cu / Mg / Al five-element layered double hydroxide material, The molar ratio of Ni to Fe is 1:0.95-1.05; and / or The molar ratio of Ni to Cu is 1:0.95-1.05; and / or The molar ratio of Ni to Mg is 1:14-18; and / or The molar ratio of Ni to Al is 1:3-5.

7. The preparation method according to claim 5 or 6, wherein: When M is selected from VIB group metal elements and IVA group metal elements, the contact conditions include: temperature of 60-70° C., time of 14-18 hours, pH of 9-11; and / or In the metal salt solution containing M, the concentration of the M element is 0.03-0.05 mol / L; and / or When M is selected from VA group metal elements, the ball milling conditions include: a rotation speed of 400-500 rpm and a time of 1-1.5 h.

8. The preparation method according to any one of claims 4 to 7, wherein: The ion exchange conditions include: temperature 30-60°C, time 8-36h; and / or The reduction conditions include: a temperature of 800-1000° C.; and / or a reduction time of 3-5 h.

9. The hydrogenation catalyst prepared by the preparation method according to any one of claims 4 to 8.

10. Use of the hydrogenation catalyst according to any one of claims 1 to 3 and 9 in the hydrogenation of alkynes to produce olefins; Preferably, the application includes: In the presence of a catalyst, a feed gas containing alkynes is subjected to a hydrogenation reaction; the catalyst comprises the hydrogenation catalyst according to any one of claims 1 to 3 and 9; Preferably, the volume ratio of alkyne to hydrogen is 1:5-100; Preferably, the concentration of alkyne in the alkyne-containing feed gas is 0.5-1.0% by volume; Preferably, the alkyne-containing feed gas contains 5-60% by volume of olefins having the same number of carbon atoms as the alkyne; Preferably, the alkyne-containing feed gas comes from petroleum fraction cracking gas; Preferably, the gas phase space velocity is 4000-4600h -1 ; Preferably, the hydrogenation conditions include: a temperature of 20-130°C, preferably 70-130°C; and / or The pressure is 0.1-0.2MPa.